Association between Adipokines and Biomarkers of Alzheimer's Disease: A Cross-Sectional Study. - Letra, Liliana; Matafome, Paulo; Rodrigues, Tiago; Duro, Diana; Lemos, Raquel; Baldeiras, Ines; Patrício, Miguel; Castelo-Branco, Miguel; Caetano, Gina; Seiça, Raquel; Santana, Isabel (J Alzheimers Dis, 2019)
BACKGROUND: Adipose tissue dysfunction has been implicated in the pathophysiology of Alzheimer's disease. However, the involvement of adipokines, particularly adiponectin, remains unclear. OBJECTIVE: To compare serum and cerebrospinal fluid (CSF) levels of adiponectin, leptin and leptin-to-adiponectin ratio in patients within the spectrum of Alzheimer's disease and evaluate their relationship with classical biomarkers and their value as markers of progression. METHODS: Amnestic mild cognitive impairment (MCI, n = 71) and Alzheimer's dementia (AD, n = 53) subjects were consecutively recruited for serum and CSF adiponectin and leptin determination using an analytically validated commercial enzyme-linked immunosorbent assay (ELISA). Correlations were explored using adjusted Spearman's correlation coefficients. A logistic regression model and ROC analysis were performed to evaluate the staging predictive value of adipokines. RESULTS: Serum adiponectin was 33% higher in AD when compared to MCI patients. Adiponectin CSF levels, similar in both groups, were positively correlated with Aβ42 and cognitive function, though only in women. The area under the ROC curve was 0.673 (95% CI:0.57-0.78) for serum adiponectin as predictor of dementia stage and the cut-off 10.85μg/ml maximized the sum of specificity (87%) and sensitivity (44%). CONCLUSION: Although longitudinal studies are required, we hypothesize that higher serum adiponectin in AD patients constitutes a strategy to compensate possible central signaling defects. In addition, adiponectin might be specifically assigned to neuroprotective functions in women and eventually involved in the female-biased incidence of Alzheimer's disease.

Can 11C-PiB-PET Relative Delivery R1 or 11C-PiB-PET Perfusion Replace 18F-FDG-PET in the Assessment of Brain Neurodegeneration? - Oliveira, Francisco P M; Moreira, Ana Paula; de Mendonça, Alexandre; Verdelho, Ana; Xavier, Carolina; Barroca, Dalila; Rio, Joana; Cardoso, Eva; Cruz, Ângela; Abrunhosa, Antero; Castelo-Branco, Miguel (J Alzheimers Dis, 2018)
BACKGROUND: Pittsburgh Compound B (PiB) positron emission tomography (PET) is used to visualize in vivo amyloid plaques in the brain. Frequently the PiB examinations are complemented with a fluorodeoxyglucose (FDG) PET scan to further assess neurodegeneration. OBJECTIVE: Our goal is to identify alternative correlates of FDG images by assessing which kinetic methods originate PiB derived relative delivery ratio (R1) images that can be correlated with the FDG images, and to compare them with PiB perfusion (pPiB) images obtained from the early-phase of PiB acquisition. METHODS: We selected 52 patients with cognitive impairment who underwent a dynamic PiB and FDG acquisitions. To compute the R1 images, two simplified reference tissue models (SRTM and SRTM2) and two multi-linear reference tissue models (MRTM and MRTM2) were used. The pPiB images were obtained in two different time intervals. RESULTS: All six types of images were of good quality and highly correlated with the FDG images (mean voxelwise within-subjects r > 0.92). The higher correlation was found for FDG-R1(MRTM). Regarding the voxelwise regional correlation, the higher mean all brain correlations was r = 0.825 for FDG-R1(MRTM) and statistically significant in the whole brain analysis. CONCLUSION: All R1 and pPiB images here tested have potential to assess the metabolic impact of neurodegeneration almost as reliably as the FDG images. However, this is not enough to validate these images for a single-subject analysis compared with the FDG image, and thus they cannot yet be used clinically to replace the FDG image before such evaluation.

Improved Cerebrospinal Fluid-Based Discrimination between Alzheimer's Disease Patients and Controls after Correction for Ventricular Volumes. - van Waalwijk van Doorn, Linda J C; Gispert, Juan D; Kuiperij, H Bea; Claassen, Jurgen A H R; Arighi, Andrea; Baldeiras, Ines; Blennow, Kaj; Bozzali, Marco; Castelo-Branco, Miguel; Cavedo, Enrica; Emek-Savaş, Derya D; Eren, Erden; et al. (J Alzheimers Dis, 2017)
Cerebrospinal fluid (CSF) biomarkers may support the diagnosis of Alzheimer's disease (AD). We studied if the diagnostic power of AD CSF biomarker concentrations, i.e., Aβ42, total tau (t-tau), and phosphorylated tau (p-tau), is affected by differences in lateral ventricular volume (VV), using CSF biomarker data and magnetic resonance imaging (MRI) scans of 730 subjects, from 13 European Memory Clinics. We developed a Matlab-algorithm for standardized automated segmentation analysis of T1 weighted MRI scans in SPM8 for determining VV, and computed its ratio with total intracranial volume (TIV) as proxy for total CSF volume. The diagnostic power of CSF biomarkers (and their combination), either corrected for VV/TIV ratio or not, was determined by ROC analysis. CSF Aβ42 levels inversely correlated to VV/TIV in the whole study population (Aβ42: r = -0.28; p < 0.0001). For CSF t-tau and p-tau, this association only reached statistical significance in the combined MCI and AD group (t-tau: r = -0.15; p-tau: r = -0.13; both p < 0.01). Correction for differences in VV/TIV improved the differentiation of AD versus controls based on CSF Aβ42 alone (AUC: 0.75 versus 0.81) or in combination with t-tau (AUC: 0.81 versus 0.91). In conclusion, differences in VV may be an important confounder in interpreting CSF Aβ42 levels.